The cost of democracy: The determinants of spending on the public administration of elections - Clark, Alistair (International Political Science Review)
Managing the electoral process requires considerable administrative and organizational capacity. Poor performance can lead to voters being disenfranchised and the integrity and legitimacy of elections undermined. Providing sufficient capacity to manage a national electoral process is expensive. Little research assesses how much electoral democracy costs, and what drives those costs. These are crucial questions for democracies, political science and public administration. Using rare comprehensive data from Britain, this article$1 (Bs major contribution is to begin identifying some of the drivers impacting on the cost of electoral administration in advanced democracies. It presents an overview of influences on spending on electoral administration, before developing a multivariate model utilizing socio-economic, organizational and administrative data on election spending. It finds that costs in an important advanced democracy have been driven in a major national election by the need to provide capacity, notably on the ground close to electors. - Reproduced.s
Keywords: Elections; Electoral administration; Electoral integrity